The Effect Of Mobile Banking Product Quality On Customer Satisfaction Of Indonesian Sharia Bank Jakarta Wolter Monginsidi Branch - Gani Wiharso; Johan Hendri Prasetyo; Bobby Suryo Prakoso; Luky Fabrianto (Matriks Jurnal Sosial dan Sains, 2022)
Bank is a financial institution that collects funds from the public in the form of deposits, both demand deposits, savings and time deposits. This study aims to determine the effect of mobile banking product quality on customer satisfaction of Bank Syariah Indonesia Jakarta branch Wolter Monginsidi. The method use is a survey methode using descriptive and verification analysis technique. The sampling technique of this study used a purposive sampling technique of 75 respondents.  The data collection technique use quisionnaire with 20 question items assessed on a Likert scale 1-5 and tested for validity and reliability. Hyphotesis testing using statistical analysis included classical assumption test (Normality test and Heteroscedasticity test), Autocorrelation test (Dubin Watson), Simple Linier Regression Analysis (R square, t-test, and F test). Based on partial test, it can be stated that Product Quality has a positive effect on visitors to the Jakarta branch of Bank Syariah Indonesia Wolter Monginsidi, so the hypothesis can be accepted.